Diet, life expectancy, and chronic disease : studies of Seventh-Day Adventists and other vegetarians - Fraser, Gary E. (Oxford University Press, 2003)
Research into the role of diet in chronic disease can be difficult to interpret. Measurement errors in different studies often produce conflicting answers to the same questions. Seventh-day Adventists and other groups with many vegetarian members are ideal study populations because they have a wide range of dietary habits that adds power and clarity to research findings. This book analyses the results of such studies, focusing on heart disease and cancer. These studies support the benefits of a vegetarian diet and in addition provide evidence about the effects of individual foods and food groups on disease risk that is relevant to all who are interested in good health. The author places the findings in the broader context of well-designed nutritional studies of the general population. He discusses the degree of confidence we can have in particular relationships between diet and disease based on the strength of the evidence. The book is written in a clear style with an extensive glossary, and should be accessible to a wide audience.